Production and heat treatment of cast graphitic steels with additions of niobium - Soufen, C. A. [UNESP]; Casteletti, L. C.; Neto, A. Lombardi; Totten, G. E. (My University, 2006)
The optimal combination of the mechanical characteristics of austempered spheroidal graphitic cast steel together with modern casting techniques yielded an economically promising product. The maximum potential of the usage of these steels is related to fabrication and characterization techniques, among which, one of the most important is the cooling diagram (TTT curve). In this work, 3 heats of graphitic steels with the following nominal compositions were cast: 1.0 % C, 2.3 % Si, 0.4 % Mn, and with niobium contents of. 0.0 %, 0.5 % and 1.0 %. TTT curves were determined by dilatometric testing and test specimens of these steels were austempered. The samples were then characterized by hardness testing and optical and SEM microscopy. Tensile, impact (no notch) and wear testing were also performed. The addition of niobium produced significant alterations in the TTT diagrams. Increasing niobium content moves the pearlite transformation nose to the right and the bainitic transformation nose to the left. Tensile strength of these alloys was high, in the range of 1700 MPa and impact values were around of 45 Joules for alloy with 1 % Nb, 49 Joules for alloy with 0.5 % Nb and fracture did not occur for the alloy without the addition of Nb.
Keywords: Alloys; Bainitic transformations; Fracture fixation; Hardness testing; Heat treating furnaces; Heat treatment; Impact strength; Impact testing; Manganese; Manganese compounds; Metallic compounds; Niobium; Optical design; Optical microscopy; Optical testing; Pearlitic transformations; Quenching; Silicon; Steel metallurgy; Surface analysis; Surface treatment; Technology; Tensile testing; Transition metals; Cast steels; Casting techniques; Characterization techniques; Graphitic steels; Impact values; International Federation for Heat Treatment; Mechanical characteristics; Niobium content; Nominal compositions; Optical-; Optimal combinations; Surface engineering; Test specimens; TTT curves; TTT diagrams; Wear testing; Steel castings